SCHEDULING SIMULTANEOUS PROJECTS OPERATION BASET ON THE AVAILABILITY OF THE CONSTRUCTIONSOURSES - Mawardi Mawardi (Jurnal Teknologi Berkelanjutan, 2012)
The research aims at analysing simultaneous projects scheduling based on the availability of construction sources of equipment owned by contractors. The research mainly discusses about how simultaneous projects schedule based on the availability of equipment owned is arranged. The approach used in this research is construction project schedule modelling where construction projects are carried out using a certain project management system. Based on the analysis result, it is obtained that the project schedule is arranged by employing precedent diagram. Project equipment transporting matrix is used as an alternative to schedule simultaneous projects. Both of these instruments provide information about the type of works, timetable, project location and project equipment arrangement. The project schedule is arranged based on job package and project location. For the first job package both the schedule and the equipment transporting arrangement are scheduled. In this job package, there are only five locations located in the same area. The second job package consists of nine scattered locations. As a result, a stricter schedule and equipment transporting arrangement are required. It is expected that this research can be used as a guide in analysing simultaneous project schedule so that good quality and efficiency can be acquired, at the same time loss and inefficiency can be minimised. Transporting equipment is an important aspect of the project that must be put into consideration. For future researches, it is expected that this research can be developed using research models which are more complex and accurate